D‐cycloserine combined with cue exposure therapy fails to attenuate subjective and physiological craving in cocaine dependence. (24th March 2015) - Santa Ana, Elizabeth J.; Prisciandaro, James J.; Saladin, Michael E.; McRae‐Clark, Aimee L.; Shaftman, Stephanie R.; Nietert, Paul J.; Brady, Kathleen T.
Abstract : Background: Based on preclinical studies showing that the partial N ‐methyl‐D‐aspartate (NMDA) agonist D‐cycloserine (DCS) facilitates extinction of cocaine self‐administration and cocaine‐induced conditioned place preference, we evaluated whether 50 mg of DCS would reduce craving to cocaine cues when combined with cue exposure (CE) in cocaine dependent humans. Methods: In this double‐blind placebo‐controlled pilot study, 47 cocaine dependent participants were randomized to DCS or placebo (PBO), plus CE. Participants received DCS or PBO 30 minutes prior to two CE sessions, conducted one day apart. Craving and heart rate was assessed prior to CE sessions, during CE trials, and after CE trials. These measures were assessed again at a 1‐week follow‐up (session 3) after the second CE session. Results: DCS failed to significantly attenuate cocaine cue reactivity based on subjective craving and physiological reactivity (heart rate) compared to PBO. The CE protocol, consisting of repeated exposure to drug cues combined with skills training, resulted in extinction to cocaine cues as suggested by decreased craving within and between sessions in both treatment conditions. All participants exhibited elevated heart rate with repeated exposures, demonstrating a potentiation in heart rate between sessions. Conclusions: 50 mg of DCS may not be effective for extinguishing reactivity to drug cues for individuals with cocaine dependence. Scientific Significance: Future studies examining the effect of DCS on facilitating extinction to drug cues should examine variations in cue exposure length, number of CE presentations, and timing of DCS dose administration prior to cue exposures, which may differentially impact drug cue reactivity. (Am J Addict 2015;24:217–224)